2015
DOI: 10.3390/ijms16035839
|View full text |Cite
|
Sign up to set email alerts
|

The CENP-T C-Terminus Is Exclusively Proximal to H3.1 and not to H3.2 or H3.3

Abstract: The kinetochore proteins assemble onto centromeric chromatin and regulate DNA segregation during cell division. The inner kinetochore proteins bind centromeres while most outer kinetochore proteins assemble at centromeres during mitosis, connecting the complex to microtubules. The centromere–kinetochore complex contains specific nucleosomes and nucleosomal particles. CENP-A replaces canonical H3 in centromeric nucleosomes, defining centromeric chromatin. Next to CENP-A, the CCAN multi-protein complex settles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 127 publications
1
3
0
Order By: Relevance
“…This is consistent with recent reports that predict that CENP-T/-W and CENP-S/-X are part of separate protein cohorts within the kinetochore (Samejima et al 2015). In agreement with previous reports regarding CENP-T/-W interactions, we did not find CenH3 CENP-A in our CENP-W-GFP pull-downs (Hori et al 2008;Abendroth et al 2015), confirming the specificity of our approach. The presence of both FACT chaperone complex subunits (SSRP1 and Spt16) in both the low-salt and high-salt sample fractions of our MS analysis caught our attention, especially given that FACT has previously been reported as a component of centromeric chromatin pull-downs where CENP-T (also annotated as ICEN22/ FLJ13111) was also found (Foltz et al 2006;Izuta et al 2006).…”
Section: Fact Subunits Interact With the Cenp-t/-w Complexsupporting
confidence: 82%
“…This is consistent with recent reports that predict that CENP-T/-W and CENP-S/-X are part of separate protein cohorts within the kinetochore (Samejima et al 2015). In agreement with previous reports regarding CENP-T/-W interactions, we did not find CenH3 CENP-A in our CENP-W-GFP pull-downs (Hori et al 2008;Abendroth et al 2015), confirming the specificity of our approach. The presence of both FACT chaperone complex subunits (SSRP1 and Spt16) in both the low-salt and high-salt sample fractions of our MS analysis caught our attention, especially given that FACT has previously been reported as a component of centromeric chromatin pull-downs where CENP-T (also annotated as ICEN22/ FLJ13111) was also found (Foltz et al 2006;Izuta et al 2006).…”
Section: Fact Subunits Interact With the Cenp-t/-w Complexsupporting
confidence: 82%
“…This substitution could trigger changes in molecular properties of H3.1, which makes it distinguishable from H3.2, as evident by a specific elution profile using HPLC. A possible explanation may be that this residue is a site for post-translational modification, and therefore, could alter the structure and/or dynamics ( 60–62 ). Another study has shown that this substitution can significantly increase the stability of the tetramer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the technique has demonstrated, to be a valuable tool in our study the centromeric chromatin (Llères et al, 2009). This is the chromatin site where the kinetochore structure is anchored by the presence of CENP-A histone and longer links made possible by the CENP-C terminal tails as we have reported in Abendroth et al (2015). A combination of the STORM and FRET in the study kinetochore structure and centromeric chromatin is expected to be a major breakthrough in understanding of these highly dynamic structures in the cell cycle.…”
Section: Optical Microscopy Approaching To Nanoscopymentioning
confidence: 80%